Analisis Implementasi Akad Murabahah Dalam Pembiayaan Konsumtif Di Bank Syariah - Mulki Akhdan; Mohd Winario; Mifta Hasda; Muhammad Syaipudin; Rifqil Khairi (EL-EMIR Institute, 2026)
The development of Islamic financing in Indonesia has positioned the murabahah contract as the dominant instrument in consumer financing. However, its implementation still raises several issues related to ownership of goods, margin transparency, and potential procedural deviations. This study aims to evaluate the implementation of murabahah contracts in consumer financing within Islamic banking and to assess their compliance with Sharia principles and the provisions of the DSN-MUI Fatwa. The research employs a qualitative approach using an explanatory case study through literature review and normative analysis of regulations and operational practices. The findings indicate that, conceptually, murabahah contracts have been systematically implemented through mechanisms involving the bank’s purchase of goods, transparent margin determination, and installment payments agreed upon by both parties. Nevertheless, several challenges remain, including practices that tend to resemble conventional credit systems and the limited understanding of Sharia principles among some transaction participants. This study highlights the importance of strengthening Sharia supervision, improving customer literacy, and optimizing financing governance to ensure that murabahah contracts maintain integrity, fairness, and accountability within the Islamic financial system.